Anisotropic corrosion behavior of hot-rolled Mg-8 wt.%Li alloy. (15th September 2020) - Wang, Baojie; Xu, Kai; Xu, Daokui; Cai, Xiang; Qiao, Yanxin; Sheng, Liyuan
Abstract: By performing the immersion, hydrogen evolution and electrochemical corrosion testing in a 0.1 mol/L NaCl solution, the corrosion performance of differently oriented samples cut from an as-rolled Mg-8 wt.%Li alloy plate has been investigated and compared. It demonstrated that obvious anisotropy in corrosion resistance existed between the sample surfaces with different orientations. Among them, the corrosion rate of "ND" (the normal direction) samples with their surfaces perpendicular to the normal direction of the plate was the highest. The corrosion rate of "TD" (the transverse direction) samples with their surfaces perpendicular to the transverse direction of the plate took the second place. For the "RD" (the rolling direction) samples with their surfaces perpendicular to the rolling direction of the plate, they had the lowest corrosion rate. For all the samples, their corrosion performance and the pitting severity were mainly ascribed to the crystallographic texture of α-Mg matrix phases because the formed surface films on β-Li phases could provide good protection to the substrate. For the "ND" and "TD" samples, the exposed surfaces were composed of {0002}, {10 1 ¯ 0} and {11 2 ¯ 0} planes of α-Mg phases and subsequently resulted in their severe corrosion attack due to the corrosion couples between basal and prism planes. Since the crystallographic planes of exposed α-Mg phases on the surfaces of "RD" samples were mainly {10 1 ¯ 0} and {11 2 ¯ 0} prism planes, the pitting severity was the weakest.